Implementation Of Digital Technology For Management Opti-mization Production In The Palm Oil Industry (Case Study of Employees of PT. Perkebunan Nusantara IV PKS SEI Meranti) - Pernando Simanjuntak; Aulia Indra; Yuniman Zebua (International Journal of Business and Quality Research, 2026)
This study aims to analyze the implementation of digital technology in optimizing production management in the palm oil industry with a case study of employees at PT. Perkebunan Nusantara IV PKS Sei Meranti. This research used a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving five informants who were directly involved in production activities. The results show that digital technology implementation has been carried out through the digitalization of production systems, the use of Internet of Things (IoT), digital-based production monitoring, and production management information systems. The application of these technologies improves production efficiency, accelerates data processing and access, enhances quality control, and supports data-based decision making. However, several challenges were identified, including limited employee skills in operating digital systems, network disruptions, and high investment costs for technology development. Therefore, the company conducts various efforts such as employee training, regular system maintenance, and improvement of technological facilities to support the optimization of production management. This study indicates that digital technology plays an important role in improving efficiency, productivity, and effectiveness of production management in the palm oil industry.